A review of family caregiving intervention trials in oncology. (20th March 2017) - Ferrell, Betty; Wittenberg, Elaine
Abstract: This article contains a review of literature published from 2010 to 2016 on family caregiving in oncology. An analysis of 810 citations resulted in 50 randomized trials. These trials describe the need to prepare family caregivers for the complex role they play in cancer care. Several studies have demonstrated improved quality of life for family caregivers and improved emotional support from interventions. Several studies addressed communication and relational intimacy, which are key concerns. An additional focus of these trials was in the area of caregiving tasks and ways to diminish the burden of caregiving and preparedness for this role. Further research is needed in this area given the shift to outpatient care and as family caregivers become the primary providers of care. Future research should include expanding tested models of family caregiver support in clinical practice and in diverse populations. CA Cancer J Clin 2017. © 2017 American Cancer Society.CA Cancer J Clin 2017;67:318–325. © 2017 American Cancer Society.